EU Directive 2008/50/EC on Ambient Air Quality and Cleaner Air for Europe in Context of the Republic of Macedonia - Rumenov, Ilija; Toceva, Martina; Mitreski, Kosta (Faculty of Computer Science and Engineering, Skopje, Macedonia Ss. Cyril and Methodius University in Skopje, Macedonia, 2018)
The EU Directive 2008/50/EC on ambient air quality and cleaner air for Europe provides for rules in order to reduce pollution to levels which minimize harmful effects on human health, paying particular attention to sensitive populations and to improve the monitoring and assessment of air quality including the deposition of pollutants and to provide information to the public. This article provides for analysis of the ambient air quality and measurement systems in the Republic of Macedonia in context of this EU Directive and it offers for examination of the Directive requirements in respect of air quality management area delineation - zones and agglomerations. The evaluation is made on the basis of the regular measurements obtained from the existing measuring networks as well as via measurements of the emissions from stationary and mobile sources in several years period. Results from the analysis of air pollution parameters SO2, NO2, NOx, PM10 and ozone concentrations are presented both for specific regions and on the entire state territory.
Keywords: EU directives, air pollution, zones, models